Improvement of Acetaldehyde Production in Zymomonas mobilis by Engineering of Its Aerobic Metabolism - Kalnenieks, Uldis; Balodite, Elina; Strähler, Steffi; Strazdina, Inese; Rex, Julia; Pentjuss, Agris; Fuchino, Katsuya; Bruheim, Per; Rutkis, Reinis; Pappas, Katherine M.; Poole, Robert K.; Sawodny, Oliver; et al. (Frontiers in Microbiology, 2019)
Acetaldehyde is a valuable product of microbial biosynthesis, which can be used by the chemical industry as the entry point for production of various commodity chemicals. In ethanologenic microorganisms, like yeast or the bacterium Zymomonas mobilis, this compound is the immediate metabolic precursor of ethanol. In aerobic cultures of Z. mobilis, it accumulates as a volatile, inhibitory byproduct, due to the withdrawal of reducing equivalents from the alcohol dehydrogenase reaction by respiration. The active respiratory chain of Z. mobilis with its low energy-coupling efficiency is well suited for regeneration of NAD+ under conditions when acetaldehyde, but not ethanol, is the desired catabolic product. In the present work, we sought to improve the capacity Z. mobilis to synthesize acetaldehyde, based on predictions of a stoichiometric model of its central metabolism developed herein. According to the model analysis, the main objectives in the course of engineering acetaldehyde producer strains were determined to be: (i) reducing ethanol synthesis via reducing the activity of alcohol dehydrogenase (ADH), and (ii) enhancing the respiratory capacity, either by overexpression of the respiratory NADH dehydrogenase (NDH), or by mutation of other components of respiratory metabolism. Several mutants with elevated respiration rate, decreased alcohol dehydrogenase activity, or a combination of both, were obtained. They were extensively characterized by determining their growth rates, product yields, oxygen consumption rates, ADH and NDH activities, transcription levels of key catabolic genes, as well as concentrations of central metabolites under aerobic culture conditions. Two mutant strains were selected, with acetaldehyde yield close to 70 % of the theoretical maximum value, almost twice the previously published yield for Z. mobilis. These strains can serve as a basis for further development of industrial acetaldehyde producers.